2021
DOI: 10.1002/art.41937
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immune Response and Disease Status in Systemic Lupus Erythematosus Patients Following SARSCoV‐2 Vaccination

Abstract: Objective To evaluate seroreactivity and disease flares after COVID‐19 vaccination in a multi‐ethnic/racial cohort of patients with systemic lupus erythematosus (SLE). Methods 90 SLE patients and 20 healthy controls receiving a complete COVID‐19 vaccine regimen were included. IgG seroreactivity to the SARS‐CoV‐2 spike receptor‐binding domain (RBD) and SARS‐CoV‐2 microneutralization were used to evaluate B cell responses; IFN‐γ production to assess T cell responses was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
135
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(166 citation statements)
references
References 33 publications
15
135
2
1
Order By: Relevance
“…The vast majority of included studies evaluated vaccines developed by Pfizer (BNT162b2) or Moderna (mRNA-1273). Thirteen studies included patients who received the vaccine developed by Janssen (Ad26.COV2.S) [ [25] , [26] , [27] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ], nine included patients vaccinated with the AstraZeneca vaccine (ChAdOx1) [ [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ], three included patients receiving the CoronaVac vaccine (Sinovac Biotech) [ [50] , [51] , [52] ], and one randomized controlled trial evaluated the vaccine developed by Novavax (NVX-CoV2373) vaccine [ 53 ]. One study included patients receiving the BBV152-Covaxin (Bharat Biotech) vaccine [ 44 ] and one included patients receiving the BBIBP-CorV (Sinopharm) vaccine [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The vast majority of included studies evaluated vaccines developed by Pfizer (BNT162b2) or Moderna (mRNA-1273). Thirteen studies included patients who received the vaccine developed by Janssen (Ad26.COV2.S) [ [25] , [26] , [27] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ], nine included patients vaccinated with the AstraZeneca vaccine (ChAdOx1) [ [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ], three included patients receiving the CoronaVac vaccine (Sinovac Biotech) [ [50] , [51] , [52] ], and one randomized controlled trial evaluated the vaccine developed by Novavax (NVX-CoV2373) vaccine [ 53 ]. One study included patients receiving the BBV152-Covaxin (Bharat Biotech) vaccine [ 44 ] and one included patients receiving the BBIBP-CorV (Sinopharm) vaccine [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies assessed anti-SARS-CoV-2 immunity through an immunoassay to detect antibodies targeted at the spike protein, including some targeting specifically the receptor-binding domain (RBD) of the spike protein. Thirty studies reported neutralization assay results in addition to anti-SARS-CoV-2 antibody assays [ 34 , 37 , 41 , 48 , 51 , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ]. Thirty-one studies provided data on cellular immunity [ 17 , 21 , 22 , 34 , 37 , 41 , 45 , 46 , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , 72 , [74] , [75] , [76] , [77] , [79] , [80] , [81] , [82] , [83] , [84] ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations